P-034 Common data elements reported on middle meningeal artery embolization in chronic subdural hematoma: an interactive systematic review of recent trials. (23rd July 2022) - Adusumilli, G; Ghozy, S; Kallmes, K; Hardy, N; Tarchand, R; Zinn, C; Lamar, D; Singeltary, E; Siegel, L; Kallmes, D; Arthur, A; Gellißen, S; et al.
Abstract : Background: Cross-study heterogeneity has limited the evidence-based evaluation of middle meningeal artery embolization (MMAE) as a treatment for chronic subdural hematoma (CSDH). Ongoing trials and prospective studies suggest that heterogeneity in upcoming publications may detract from subsequent meta-analyses and systemic reviews. This study aims to describe this data heterogeneity in order to promote harmonization with common data elements (CDEs) in publications. Methods: ClinicalTrials: gov and PubMed were searched for published or ongoing prospective trials of MMAE. The Nested Knowledge AutoLit living review platform was utilized to classify endpoints from randomized control trials (RCT) and prospective cohort studies comparing MMAE to other treatments. The Qualitative Synthesis feature was used to determine cross-study overlap of outcome-related data elements. Results: Eighteen studies were included: twelve RCTs, two non-randomized controlled studies, two prospective single-arm trials, one combined prospective and retrospective controlled study, and one prospective cohort study. The most commonly reported data element was recurrence (15/18), but seven heterogenous (non-comparable) definitions were employed for 'recurrence.' Mortality was reported in 10/18 studies, but no common timepoint was reported in more than four studies. Re-intervention and CSDH volume were reported in eight studies, CSDH width in seven, and no other outcome was common across more than five studies. Conclusions: There was significant heterogeneity in data element collection even among prospective, registered trials of MMAE. Even among CDEs, variation in definition and timepoints prevented harmonization. A standardized approach based on CDEs may be necessary to facilitate future meta-analyses and evidence-driven evaluation of MMAE treatment of CSDH. Disclosures: G. Adusumilli: None. S. Ghozy: None. K. Kallmes: 4; C; Nested Knowledge, Inc, Superior Medical Experts, Inc. 5; C; Nested Knowledge, Inc, Conway Medical LLC. N. Hardy: 4; C; Nested Knowledge, Inc. 5; C; Nested Knowledge, Inc. R. Tarchand: None. C. Zinn: None. D. Lamar: None. E. Singeltary: 5; C; Nested Knowledge, Inc. L. Siegel: 5; C; Nested Knowledge, Inc. D. Kallmes: 1; C; Microvention, Balt USA, Medtronic. 4; C; Nested Knowledge, Inc, Superior Medical Experts, Inc, Conway Medical LLC. A. Arthur: 1; C; STEM Trial. S. Gellißen: None. J. Fiehler: 1; C; Imaging Core Lab for EMBOLISE, German Ministry of Science and Education, German Ministry of Economy and Innovation, German Research Foundation, European Union, Hamburgische Investition- und Förderbank, Medtronic, Microvention, Route92, Stryker. 2; C; Acandis, Bayer, Boehringer Ingelheim, Cerenovus, Covidien, Medtronic, Medina, Microvention, Penumbra, Phenox, Stryker, Transverse Medical. 4; C; Tegus Medical. J. Heit: 1; C; iSchemaView.. 2; C; Medtronic, Microvention.